2016
DOI: 10.1002/cncr.29956
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes with concurrent chemoradiation for elderly patients with locally advanced head and neck cancer according to the National Cancer Data Base

Abstract: Precis: Patients older than 70 years should not be denied concurrent chemotherapy with radiation for locally-advanced HNSCC. Additional factors including performance status and tumor stage ought to be accounted for. AbstractBackground: The overall survival (OS) benefit of concurrent chemotherapy plus radiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 37 publications
9
85
0
2
Order By: Relevance
“…Given the radical changes in the epidemiology of HNSCC in developed countries, the shift in causative risk factors, and improvements in RT delivery, it is possible that the therapeutic ratio for treatment intensification in older adults with HNSCC is somewhat more favorable in the modern era. 53,54 …”
Section: Methodsmentioning
confidence: 99%
“…Given the radical changes in the epidemiology of HNSCC in developed countries, the shift in causative risk factors, and improvements in RT delivery, it is possible that the therapeutic ratio for treatment intensification in older adults with HNSCC is somewhat more favorable in the modern era. 53,54 …”
Section: Methodsmentioning
confidence: 99%
“…A large meta-analysis of chemotherapy in nonmetastatic head and neck cancer found that concurrent chemotherapy with radiation therapy (CRT) significantly improved survival among all comers, but a subset analysis did not find a statistically significant benefit to chemotherapy for patients aged >70 years (7). Contrary to these findings, a recently published cohort study using the National Cancer Data Base (NCDB) revealed that elderly patients might still benefit from concurrent chemotherapy when treated with radiation therapy (RT) in the definitive setting (8). A propensity score—matched analysis, controlling for patient and tumor characteristics, demonstrated a 5-year absolute survival difference of 15% in favor of CRT compared with RT alone among patients aged >70 years.…”
Section: Introductionmentioning
confidence: 95%
“…Se analizó el beneficio de la quimioterapia para cada localización en la supervivencia global, observándose en el grupo de tumores de hipofaringe que la supervivencia a los 5 años era un 3,9 % mejor en aquellos pacientes que habían recibido quimioterapia concomitante. 20 Se han publicado estudios no aleatorizados, algunos específicos en cánceres de la laringe, otros de la hipofaringe [21][22][23][24] y otros mezclando cánceres de laringe e hipofaringe 25,26 . Beauvillain et al 21 compararon los resultados del tratamiento conservador frente a la cirugía radical en tumores resecables de hipofaringe; establecieron dos grupos, el primero tratado con quimioterapia de inducción seguida de cirugía radical con radioterapia postoperatoria y el segundo tratado con quimioterapia de inducción seguida de radioterapia.…”
Section: Discussionunclassified
“…Por lo que no debemos extrapolar los resultados de Hoffman et al 26 al cáncer de hipofaringe, sin embargo, nos recuerda que la QRT ofrece resultados oncológicos similares a la LT pero no superiores.…”
Section: Discussionunclassified